2024
DOI: 10.1039/d3nr05495k
|View full text |Cite
|
Sign up to set email alerts
|

Protein-guided biomimetic nanomaterials: a versatile theranostic nanoplatform for biomedical applications

Da-Gui Zhang,
Yu-Jing Pan,
Biao-Qi Chen
et al.

Abstract: Over the years, bioinspired mineralization-based approaches have been applied to synthesize multifunctional organic-inorganic nanocomposites. These nanocomposites can address the growing demands of modern biomedical applications. Proteins, serving as vital biological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Protein encapsulation in ZIF-8 nanoparticles has been demonstrated to protect protein structure and function, and enhance protein activity. [12][13][14] However, the application of protein@ZIF-8 materials in biological applications is limited by the degradation of ZIF-8 in aqueous buffered solutions. 8,9,15 Vasquez-Hernandez et al demonstrated that ZIF-8 degrades in phosphate buffered saline (PBS) due to the chelation of phosphate ions to Zn nodes ultimately causing the de-coordination of ZIF-8.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Protein encapsulation in ZIF-8 nanoparticles has been demonstrated to protect protein structure and function, and enhance protein activity. [12][13][14] However, the application of protein@ZIF-8 materials in biological applications is limited by the degradation of ZIF-8 in aqueous buffered solutions. 8,9,15 Vasquez-Hernandez et al demonstrated that ZIF-8 degrades in phosphate buffered saline (PBS) due to the chelation of phosphate ions to Zn nodes ultimately causing the de-coordination of ZIF-8.…”
Section: Introductionmentioning
confidence: 99%